Factors affecting anxiety among the tuberculosis patients in urban health clinics of Kathmandu metropolitan city. (2014)
ABSTRACT: The main objective of the study is to identify the level and factors affecting anxiety among tuberculosis patients. The study was a descriptive cross-sectional, noninterventional study conducted in Urban Health Clinics of Koteshwor, Baneshwor, Dillibazar and Mitrapark taking 96 respondents randomly. The patients included tuberculosis patients receiving CAT-I and CAT-II anti-tuberculin medicines for varied period of times. A set of semi-structured questionnaire and Hamilton Anxiety Rating Scale were used for demographic factors, level of anxiety and factors associated with anxiety. The collected data was analyzed in SPSS version 17.0. Out of 96 respondents interviewed, 37.5 % were found to be anxious and out of various variables only side-effects of medicine was positively correlated with anxiety level. 62.5% had normal anxiety level which itself is a satisfactory result. More than half of the respondents were male and more than one third respondents were of age 25-34 indicating young people suffering from TB mostly. More than half of the respondents were married and most of the respondents were Hindu. More than one fourth of the respondents were students. Almost all of them were literate. More than half of the respondents had pulmonary TB. Only 8 out of 96 respondents were smokers and smoked maximum 10 sticks per day. None of the respondents suffering from pulmonary TB smoked. Most of the respondents were under CAT-I medication. More than half of the respondents were under treatment for 2 to 6 months during the interview. Almost all of them had some kind of side effects of medicines and 17 of them had side effects non specific of anti-tuberculin drugs. 82.3% respondents only had TB while 17 respondents had other diseases like hypertension, hyperthyroidism, cancer, etc. More than 80% of respondents asserted the fact that their health was improved after medication. More than 90% of respondents' family looked after them satisfactorily after the diagnosis of the disease. Less than 10% of the respondents experienced social stigma. One third respondents lost their job and wedges after the diagnosis of TB. Half of them interpreted the response of DOTS centres' staffs' response very good. Only 5% of the respondents were anxious that TB-HIV co-infection could have occurred 62.5% respondents had only mild severity of anxiety and only 6.2% respondents had very severe anxiety. Anxiety has been positively correlated with side-effects faced due to medicines. The study can conclude that it is essential to upgrade the medicines used in Tuberculosis and make them causing fewer effects on the body and through counseling us as health care providers can minimize this burden.